Serum Magnesium Profile in different grades of malnutrition (Journal of Dhaka National Medical College & Hospital, 2016)
Background: Magnesium is the second most common intracellular cation in the body and plays an essential role in numerous biochemical reactions in vivo. Although magnesium supplementation is a time- honured pillar of management of PEM, the data on serum magnesium profile in PEM are conflicting and meagre. This study aims at evaluation of magnesium status in different grades of PEM.Objective: For better management of PEM patients, to evaluate the role of magnesium in pathophysiology of PEM.Methodology: A prospective comparative study was conducted in Dhaka. Shishu Hospital nutritional rehabilitation unit. Serum magnesium level was estimated of a total no. of 183 children, suffering from PEM.Result: Serum magnesium level of well-nourished, mildly malnourished and moderately malnourished children were 1.99 meq/L, 2.14 meq/L and 2.14 meq/L respectively. Serum magnesium level of marasmus, kwashiorkor and marasmic kwashiorkor were 2.03 meq/L, 1.95 meq/L and 1.84 meq/L respectively.Conclusion: Children suffering from oedematous malnutrition had lower serum magnesium status compared to non-oedematous malnutrition whereas magnesium status of non-oedematous malnutrition were comparable to the control groupJ. Dhaka National Med. Coll. Hos. 2016; 22 (01): 42-44